P496 Efficacy and safety of elective switching of inflammatory bowel disease patients from intravenous to subcutaneous infliximab (IFX): a multi-centre cohort study. (27th May 2021) - Smith, P J; Storey, D; Gregg, B; Critchley, L; Stenson, J; Kneebone, A; Rimmer, T; Burke, S; Hussain, S; Teoh, W Y; Vazeille, S; Serna, S; et al.
Abstract: Background: A subcutaneous (SC) formulation of IFX has recently been shown to be as effective as intravenous (IV) IFX in a randomised trial but there are no real world data to support elective switching. We aimed to assess the effectiveness of an elective switching program from IV to SC IFX in patients with IBD. Methods: Patients on maintenance IV IFX were included in this retrospective multi-centre cohort study across two sites. Disease activity was monitored serially with Harvey-Bradshaw Index (HBI) and simple clinical colitis activity index (SCCAI) at baseline, 3 and 6 months. Faecal calprotectin (FCP), C-reactive protein (CRP) and IFX levels were recorded at the same time points. Patients on 5mg/kg every 8 weeks were switched to SC IFX 120mg every other week (EOW), followed by those on 6 and 4 weekly IV IFX to either EOW or weekly SC IFX. A random selection of patients were surveyed for patient satisfaction using a likert scale. Criteria for switching were agreed within a standard operating procedure. Data was analysed using SPSS for Windows with p<0.05 being significant (ns, non-significant). Results: 172 patients (109 CD, 57 UC, 6 IBD-U) were switched to SC IFX since April 2020 (97 male vs. 75 female; mean age 39.7 years and weight 78.6kg). 57.6% patients (n=99) were on concurrent immunomodulators. 152 patients were switched to EOW dosing. From baseline to 6 months post switch, HBI, SCCAI, FCP and CRP remained stable (p>0.05, ns), but mean IFX levels significantly increased from baseline (baseline = 9.8ug/mL vs. 3 month = 14.6ug/mL; p<0.0001) and then levels remained high between 3 and 6 month follow up (6 month = 15.0ug/mL; p>0.05, ns). 8 patients (4.65%) had self-limiting skin injection site reactions, 1 UC patient (0.58%) required corticosteroids, and 2 patients (1.16%) developed perianal symptoms requiring examination under anaesthesia (EUA). Overall 4 patients (2.36%) discontinued SC treatment due to adverse events (2 perianal disease patients, 1 flaring UC patient requiring oral steroids and 1 patient with neurological symptoms) and 1 (0.58%) planned discontinuation for a patient in the 3 rd trimester of pregnancy. 85.2% (75/88) of patients agreed they were happier on SC IFX compared to IV IFX, 88.6% (78/88) feeling at least the same or better on SC IFX, and 92% (81/88) and 86.4% (76/88) agreeing that SC IFX was easy to use and felt safe using it, respectively. Conclusion: SC IFX is effective at maintaining remission in IBD patients switched from IV to SC IFX with no evidence of inferiority at 6 month follow up. There is a significant increase in IFX levels from baseline to 3 months which is maintained to 6 months post switch. SC IFX appears to be safe with low rates of adverse events and is well tolerated by patients.